Teknologi Fragmentasi Buatan Karang (Caulastrea furcata dan Cynarina lacrimalis) dalam Upaya Percepatan Pertumbuhan pada Kondisi Terkontrol - Zulfikar, Zulfikar; Soedharma, Dedi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2008)
The objective of research were analyze water quality condition of water circulation system at laboratory and tomeasured growth survival rate of Caulastrea furcata and Cynarina lacrimalis which was fragmented at laboratory.Fragmentation treatment of Caulastrea furcata become 1, 2, 3, and 4 polyp that was rearing on circulation systemdid not give significant impact on height and length growth after 160 days rearing and fragmentation of Cynarinalacrimalis on circulation system give significant impact. Mean of growth length of Caulastrea furcata on treatment1, 2, 3 and 4 polyp in every month after 160 days was 1.64 mm, 1.55 mm, 1.42 mm , and1.08 mm whereas growthbroad was 0.71 mm, 0.82 mm, 0.51 mm, 0.62 mm, and mean of growth length Cynarina lacrimalis for the sametreatment in every month was 1.47 mm, 0.90 mm, 0.62 mm, 0.61 mm whereas growth broad was 1.57 mm, 1.16mm, 0.93 mm, 0.89 mm. Fragmentation treatment of Caulastrea furcata become 1 polyp was best length if compareother treatment and Cynarina lacrimalis was treatment became 2 devide.